2012
DOI: 10.1159/000337059
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Treatment of Renal Cysts and Stones with Single-Session Retroperitoneoscopic Renal Cyst Decortication and Retroperitoneoscopy-Assisted Percutaneous Nephrolithotomy

Abstract: Introduction: To determine the safety and efficacy of single-session retroperitoneoscopic renal cyst decortication in conjunction with retroperitoneoscopy-assisted percutaneous nephrolithotomy (PCNL) for simultaneous treatment of renal cysts and stones. Patients and Methods: We enrolled 15 patients (10 men and 5 women, mean age 41 years), who underwent one-stage retroperitoneoscopic renal cyst decortication and retroperitoneoscopy-assisted PCNL between January 2008 and May 2009 for symptomatic renal cysts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For instance, a case report by Micali et al 6 described the feasibility of simultaneous laparoscopic treatment of renal stones accompanied by renal cysts. Additionally, Qiu et al 12 performed simultaneous laparoscopic cyst decortication and laparoscopy-assisted PCNL in the treatment of 15 patients with renal cysts and ipsilateral stones, achieving satisfactory stone clearance and no recurrence of cysts during a median follow-up period of 22 months. Laparoscopy offers the advantage of a high initial SFR because stones are removed without residual fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a case report by Micali et al 6 described the feasibility of simultaneous laparoscopic treatment of renal stones accompanied by renal cysts. Additionally, Qiu et al 12 performed simultaneous laparoscopic cyst decortication and laparoscopy-assisted PCNL in the treatment of 15 patients with renal cysts and ipsilateral stones, achieving satisfactory stone clearance and no recurrence of cysts during a median follow-up period of 22 months. Laparoscopy offers the advantage of a high initial SFR because stones are removed without residual fragments.…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, it is extremely challenging for surgeons to manage multiple renal stones without the assistance of percutaneous nephrolithotomy (PCNL) or flexible ureteroscopy (FURS). 11,12 Several reports have suggested that percutaneous ureteroscopy with laser unroofing or a plasma column electrode is less invasive than laparoscopy for treatment of simple renal cysts. [13][14][15][16] However, this approach has not been widely applied because of the possibility of serious postoperative complications, such as urinary leakage or massive hemorrhage requiring angio-embolization; 17,18 renal cysts and ipsilateral stones occasionally cannot be managed simultaneously through a single tract because their locations are suboptimal.…”
Section: Introductionmentioning
confidence: 99%